Transforming Organizations Through the Implementation of Processes, Structures and Relational Mechanisms for Governing IT: A Leadership Role for IS Departments in Institutions of Higher Education in Australia - Bhattacharjya, Jyotirmoyee; Chang, Vanessa (IBIMA, 2006)
Over the past decade, IT governance has become a key issue of concern for senior IT decision makers around the world. This exploratory study examines how central IS departments in four institutions of higher education in Australia are transforming organizational attitudes and approaches to governing IT by implementing structural and processes changes and establishing relational mechanisms. This paper will focus particularly on the implementation of IT governance processes in these institutions and examine how internationally recognized standards such as COBIT, ITIL and ISO17799 are being utilized. The study reveals a number of findings in the context of the implementation of IT governance in the higher education environment.